The equation 42x - 3 = 5x has to be solved.

42x - 3 = 5x

Subtract 5x from both the sides

=> 42x - 5x - 3 = 5x - 5x

=> 37x - 3 = 0

Add 3 to both the sides

=> 37x = 3

Divide both sides by 37

=> x = 3/37

**The solution of the equation is x = **`3/37`

42x - 3 = 5x

add 3 to both sides: 42x - 3 + 3 = 5x + 3

simplify: 42x = 5x + 3

subtract 5x from both sides: 42x - 5x = 5x + 3 - 5x

simplify: 37x = 3

divide both sides by 37: 37x/37 = 3/37

simplify: x = 3/37 or 0.08...

42x-3=5x

First you should add 3

Therefore, 42x=5x+3

Then minus by 5x

Therefore, 37x=3

Finally divide by 37x so your answer is 3/37 or in decimals the answer is: 0.0810810810810811

To solve for x, you first have to put x to one side, and the constants on the other side of the equation. Then, you divide the constant by the coefficient of x.

42x -3 = 5x

42x - 5x - 3 = 0 (-5x on both sides)

42x - 5x = 3 (+3 on both sides)

37x = 3 (then, divide the 3 by the coefficient of x, 37)

x = 3/37 :)